THE ROLE OF RELIGIOUS LEADERS IN PROMOTING ISLAMIC EDUCATION TO INCREASE PARTICIPATION INCONGREGATIONAL PRAYER IN RURAL COMMUNITIES - Aris Fajar Kusumah; Ferianto Ferianto; Sabariah Sulaiman (Conciencia, 2026)
This study aims to analyze the role of religious leaders in Islamic education to increase participation in congregational prayer in rural communities. Congregational prayer holds high spiritual and social value; however, participation rates in rural communities remain relatively low due to various socioeconomic and motivational factors. Religious leaders play a strategic role as educators, mentors, and role models in instilling Islamic values within the community. This study employs a descriptive qualitative approach with a phenomenological framework to deeply understand the process of Islamic education fostered by religious leaders in rural communities. Data collection techniques were conducted through observation, in-depth interviews, and documentation in Sukamanah Village, West Cikampek District. Research informants consisted of religious leaders, mosque administrators, and congregants selected using purposive sampling based on their involvement in religious activities. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions, while data validity was strengthened through triangulation of sources and methods. The results of the study indicate that religious leaders contribute significantly to the development of Islamic education through regular religious study sessions, sermons, guidance on worship, and setting a good example in daily life. This continuous guidance has proven effective in enhancing religious awareness and community participation in performing congregational prayers. Supporting factors include a religious environment, family support, and mosque facilities, while inhibiting factors include work commitments and low individual spiritual motivation. This study concludes that the success of religious leaders is determined not only by their scholarly abilities but also by the power of their exemplary conduct and a humanistic social approach in the process of community-based Islamic education. Theoretically, this study reinforces the concept of community-based non-formal Islamic education that positions religious leaders as agents of socio-religious transformation. These findings provide practical contributions to the development of a community-based Islamic education development model in rural Indonesia.